Validasi Instrumen Eksplorasi Etnomatematika pada Motif Songket Riau - Casandra, Bunga; Ediputra, Kasman; Astuti, Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims determine the validity of the instrument to be in used in ethnomathematical exploration research on the traditional musical instrument Calempong Oguong, Kampar Regency. The subjects in this study were 3 validators who were experts in their fields. This study uses validity instruments. The researrch using an interview validation sheet. Based on the results of the validation assessment of the interview sheets, the validator stated thet the interview sheets were in a very valid category, so that the interview sheets could be used to obtain data and information according to research needs.